PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PT. FAJAR MAS MURNI CABANG PEKANBARU - Zakiyah Ulfa Aryani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted to examine the effect of working capital management on profitability at PT. Fajar Mas Murni Pekanbaru Branch, located on Jalan Bindanak / Pontianak Ujung, No. 5A Tangkerang Utara, Pekanbaru, Riau. The working capital management indicators in this study are working capital turnover, cash turnover, accounts receivable turnover, and inventory turnover. And the profitability indicator is Return On Investment (ROI).               The data used in this research is secondary data. The population and sample of this study are PT. Fajar Mas Murni, Pekabaru Branch for the period 2009-2018. Data collection techniques in this study are Documentation Techniques and Key Informants. The method used is the Time Series and Cross Section data for the 2009-2018 period. Data analysis used panel test of Ordinary Least Square model with STATA 15 software program.               The results of the analysis show that working capital turnover, cash turnover, accounts receivable turnover and partial inventory turnover (t test) have a significant positive effect on ROI. The results of the simultaneous (F test) showed all independent variables significantly positive effect on ROI. The adjusted R square value of 0,844, this means working capital turnover, cash turnover, accounts receivable turnover, inventory turnover have an effect of 84,4% on profitability while the remaining 15,6% is influenced by other factors. Keywords: Working Capital Turnover, Cash Turnover, Receivables Turnover, Inventory Turnover, Profitability (ROI).